2013
DOI: 10.5539/ass.v10n1p230
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework: The Role of Microfinance on the Wellbeing of Poor People Cases Studies from Malaysia and Yemen

Abstract: The role of microfinance institutions in poverty reduction and wellbeing improvement has attracted the policymakers' attention in the developing countries across the globe as well as Malaysia and Yemen. The underlying logic is that by providing microfinance services, poor will be able to participate in the economic market through forming their small businesses. Consequently, they will be able to generate income and improve their households, self esteem and efficacy. Despite the popularity and apparent success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 38 publications
3
52
2
Order By: Relevance
“…One key informant had this to say out of the 5 total defaulters on my desk, only two are men. My findings contradicts to the findings of Mokhtar(2011), which found out that loan repayment problem was higher for males than for females, but it confirms Seyed, Majid, Nurulizwa, Mohd&Hamid (2013)and Krithie(2015 who also found that women were more likely to default on loan repayments thanmen.This default by women was associated with family responsibilities, family crisis and sickness of a family member. It comes out clearly from the key informants and the SME owners' responses that various reasons can lead to defaulting loans.…”
Section: Factors Influencing Loaned Linquencycontrasting
confidence: 90%
“…One key informant had this to say out of the 5 total defaulters on my desk, only two are men. My findings contradicts to the findings of Mokhtar(2011), which found out that loan repayment problem was higher for males than for females, but it confirms Seyed, Majid, Nurulizwa, Mohd&Hamid (2013)and Krithie(2015 who also found that women were more likely to default on loan repayments thanmen.This default by women was associated with family responsibilities, family crisis and sickness of a family member. It comes out clearly from the key informants and the SME owners' responses that various reasons can lead to defaulting loans.…”
Section: Factors Influencing Loaned Linquencycontrasting
confidence: 90%
“…Robinson (2001) has stated that welfare enhancement is not only through credit but also includes corresponding services such as skills training. Past studies have recommended that microfinance services (training) can improve the socio-economic welfare (Karlan & Valdivia 2011;Al-Mamun & Mazumder 2015;Al-Shami et al 2014). Therefore, we hypothesise the following.…”
Section: Human Capital Theorymentioning
confidence: 91%
“…As reported by recent works, the performance of Malaysian MFIs are significantly and positively linked to their clients' well-being, and better customer networks would lead to higher performing micro and small enterprises. Having such a positive relationship maximises clients' acquisition of assets and household income generation (Al-Shami, Majid, Rashid & Hamid, 2013). Hence, it is hypothesised that: H2: Customer capital (CC) is positively related to MFIs performance…”
Section: Customer Capitalmentioning
confidence: 99%